The African Charter on Democracy, Elections and Governance: a normative framework for analysing electoral democracy in Africa - Steytler, N.C. (Nico) (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2007.